A Canonical DREB2-Type Transcription Factor in Lily Is Post-translationally Regulated and Mediates Heat Stress Response - Wu, Ze; Liang, Jiahui; Zhang, Shuai; Zhang, Bing; Zhao, Qingcui; Li, Guoqing; Yang, Xi; Wang, Chengpeng; He, Junna; Yi, Mingfang (Frontiers in Plant Science, 2018)
Based on studies of monocot crops and eudicot model plants, the DREB2 class of AP2-type transcription factors have been shown to play crucial roles in various abiotic stresses, especially in the upstream of the heat stress response; however, research on DREB2s has not been reported in non-gramineous monocot plants. Here, we identified a novel DREB2 (LlDREB2B) from lily (Lilium longiflorum), which was homologous to AtDREB2A of Arabidopsis, OsDREB2B of rice, and ZmDREB2A of maize. LlDREB2B was induced by heat, cold, salt, and mannitol stress, and its protein had transcriptional activity, was located in the nucleus, was able to bind to the dehydration-responsive element (DRE), and participated in the heat-responsive pathway of HsfA3. Overexpression of LlDREB2B in Arabidopsis activated expression of downstream genes and improved thermotolerance. LlDREB2B was not regulated by alternative splicing; functional transcripts accumulated under either normal or heat-stress conditions. A potential PEST sequence was predicted in LlDREB2B, but the stability of the LlDREB2B protein was not positively affected when the predicated PEST sequence was deleted. Further analysis revealed that the predicated PEST sequence lacked a SBC or SBC-like motif allowing interaction with BPMs and required for negative regulation. Nevertheless, LlDREB2B was still regulated at the posttranslational level by interaction with AtDRIP1 and AtDRIP2 of Arabidopsis. In addition, LlDREB2B also interacted with AtRCD1 and LlRCD1 via a potential RIM motif located at amino acids 215-245. Taken together, our results show that LlDREB2B participated in the establishment of thermotolerance, and its regulation was different from that of the orthologs of gramineous and eudicot plants.